Design of Converters for PV System Under Partial Shading Conditions - M. Kowsalya; K. Balsubramanyam (Institute of Advanced Engineering and Science, 2017)
This paper presents a maximum power generation with the interconnection of photovoltaic modules under partially shaded and/or mismatching conditions. The partial shading condition reduces power level of each module. The reduction in power due to the partial shading will be compensated by the bidirectional converter. The proposed system consisting of two and three PV modules connected in series under partial shading conditions which are capable of increasing the power levels up to 50% compared to conventional by-pass diode structure. In general ‘n’ number of modules connected in series so that the maximum power gain will be expected to (100/n) %. This is achieved by developing the new control strategy in which the correct adjustment of converter duty ratio under partially shading conditions. The novel control scheme is developed by using analysis of the power converters. The proposed scheme was verified in MATLAB/SIMULINK.